Associations between language learners` spiritual intelligence, foreign language attitude and achievement motivation: A structural equation approach - Mahmoodi-Shahrebabaki, Masoud (Journal of Interdisciplinary Studies in Education, 2015)
The present study examines the relationships between language learners`Spiritual Intelligence, Achievement Motivation and Foreign LanguageAttitude. The sample consists of 223 Iranian advanced English languagelearners. The data were collected by use of Spiritual Intelligence Self-reportInventory, Foreign Language Attitude Scale and Achievement MotivationQuestionnaire. Two hypothetical models were proposed for mediation analysisby means of structural equation modeling. The results revealed that foreignlanguage attitude mediates the causal correlations between SpiritualIntelligence and Achievement Motivation. For the second model, however, theintervening effect of Achievement Motivation on the causal paths fromSpiritual Intelligence to Foreign Language Attitude was not supported basedon the analysis of effects. The results provide new insights and can pave theway for further investigation of the associations between Spiritual Intelligenceand other individual differences of language learners.